1998
DOI: 10.1002/ana.410440410
|View full text |Cite
|
Sign up to set email alerts
|

Slow vertical saccades in motor neuron disease: Correlation of structure and function

Abstract: We studied eye movements and brainstem pathology in 2 patients with slow vertical saccades and autopsy-proven amyotrophic lateral sclerosis (ALS). In both patients, the main ocular motor finding was supranuclear vertical gaze impairment with slow vertical saccades. The second patient had difficulty opening his eyes on command, with preserved spontaneous eyelid opening. Postmortem examination in both patients demonstrated cell loss in the rostral interstitial nucleus of the medial longitudinal fasciculus (riMLF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 41 publications
3
79
0
2
Order By: Relevance
“…Most patients with PSP eventually show slow [24] or absent vertical saccades, and neuropathological studies have demonstrated involvement of the region in which riMLF lies [6,9]. In addition, the localization of pathological changes in riMLF in the midbrain has been reported in two patients with ALS who had supranuclear vertical gaze impairment with slow vertical saccades [2]. Therefore, slow vertical saccades in our patients with FTD-MND could be localized to the midbrain and to the riMLF.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Most patients with PSP eventually show slow [24] or absent vertical saccades, and neuropathological studies have demonstrated involvement of the region in which riMLF lies [6,9]. In addition, the localization of pathological changes in riMLF in the midbrain has been reported in two patients with ALS who had supranuclear vertical gaze impairment with slow vertical saccades [2]. Therefore, slow vertical saccades in our patients with FTD-MND could be localized to the midbrain and to the riMLF.…”
Section: Discussionmentioning
confidence: 51%
“…All the patients who had been diagnosed as FTD-MND proved to have motor neuron degeneration [13]. Regarding the possibility that MND itself could be associated with vertical saccadic impairment, there is one report of two patients with autopsyproven MND who had slow vertical saccades and cell loss in the rostral interstitial nucleus of the medial longitudinal fasciculus (riMLF) and substantia nigra pathologically [2]. Both patients developed slow vertical eye movements three years after the onset of motor neuron disease and died five and six years after the onset of her first symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically obvious impairment in vertical eye movements is a characteristic of PSP, although it may be seen in other conditions such as diffuse Lewy body disease, 8 CBD, 72 amyotrophic lateral sclerosis, 73 post-encephalitic parkinsonism, 74 and Creutzfeld-Jacob disease. 75 In PSP, slowing of vertical saccades precedes ophthalmoplegia and is probably the earliest sign of ocular motor involvement.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…With the lack of quantifiable objective measures of disease in MND, characteristic eye movement abnormalities could be of great use both diagnostically and in research. Although eye movements are classically spared in MND some patients have been reported with a range of ocular motor disorders including nystagmus, saccadic hypometria [28], slowed saccades [8,33], increased saccadic latencies [25], decreased smooth pursuit gain [3,23,25, 32] and saccadic interruptions of smooth pursuit [20] although these studies were small and often predated the El Escorial criteria. The most comprehensive study to date [37], however, found increased antisaccadic error rates and latencies with relative preservation of reflexive saccades suggesting frontal lobe dysfunction.…”
Section: Introductionmentioning
confidence: 99%